Laundry Cashier System Application Design - Baru, Maretno Marcelina; Muhaemin, Yusup; Gumilar, Arcellia Citra Dewi; Faisal, Cepi Muhamad; Henny, Henny (International Journal of Research and Applied Technology (INJURATECH), 2025)
Databases play a crucial role in accelerating information system processes, enabling organizations to access and manage data efficiently. An integrated information system is essential for supporting operations, achieving goals, and handling large data volumes in a user-friendly manner. This study aims to replace manual service processes with computerized systems by developing a database for Mom’s Laundry to enhance service quality. Using a qualitative descriptive method, the research involved observing customer needs, conducting company surveys, identifying problems, and performing analysis. Microsoft Access was used to design the laundry’s transaction system. The study resulted in creating an automated transaction system to replace the manual process. Thus, the implementation of this database system is expected to improve efficiency, provide convenience, and deliver excellent service to customers.